HUBUNGAN PENGETAHUAN DENGAN SIKAP IBU YANG MEMPUNYAI BALITA USIA 6 – 59 BULAN TENTANG PEMBERIAN VITAMIN A DIMASA PANDEMI COVID -19 WILAYAH KERJA PUSKESMAS BABADAN KABUPATEN INDRAMAYU - Nanda Yansih Putri; Mayang Chyntaka (JURNAL KESEHATAN INDRA HUSADA, 2022)
Vitamin A is important for increasing the body's immunity, but in giving it, you must pay attention to the principle of physical distancing to prevent a wider spread. Vitamin A must be ensured to be given and consumed by toddlers 2 times a year in the month of vitamin A, namely February and August. This study uses a descriptive type with a cross-sectional design. The population in this study were all mothers who had toddlers aged 6 – 59 months in the working area of ​​the Babadan Health Center as many as 1477 people and the research sample as many as 94 people. The instrument in this study used a structured questionnaire that had been prepared. The results of the study presented distribution data in the form of a frequency table. In this study, most of the respondents 63.89% had a good knowledge category in giving vitamin A to toddlers and most of the respondents 89.4% had a supportive attitude category in giving vitamin A to toddlers. Hypothesis testing was obtained that there was a relationship between knowledge and attitudes of mothers of toddlers in giving vitamin A to toddlers. It is expected that health workers play an active role in the community, especially from community leaders to participate in providing information on vitamin A for toddlers which is given twice a year to reduce health problems in toddlers and be able to provide good immunity if given according to a predetermined schedule.